Aplicação de NURBS em MMCs, com apalpador touch trigger, para escaneamento de superfícies de formas livres e geometrias complexas - Silva, Esly César Marinho da (2011)
Nowadays the increasing demand for products with high dimensional accuracy and geometric measures has required increasingly accurate. It is necessary to use inspection systems more accurate and flexible to expect these demands. The Coordinate Measuring Machines (CMMs) are an important tool in the design, fabrication and inspection of products manufactured today. These machines are used by the engineer, whose main purpose is to produce an accurate digital model in a virtual space for later use in CAD / CAE / CAM / CAI. To identify the several shapes and surface features, there are many techniques such as Bezier surfaces, splines, B-Splines and NURBS (Non-Rational B-Splines). The NURBS present many advantages, simplicity and facility of data handling, which tends to minimize the problems of randomness and inaccuracy of the cloud of points obtained by the CMM. Thus, the NURBS are an important tool for modeling free-form, making significant contributions in reverse engineering. It is known however that the accuracy of the modeling process of a piece will be greater the larger the number of points collected or measured on the surface (whether by use of laser or continuous scanning by contact or touch point to point). Simulations results showed the effective of the proposed approach. Additionally, experimental results demonstrated that it is of practical use, non time consuming and an alternative way to apply CMMs that incorporated touch trigger probe in modeling processes. The results obtained both by simulation and experimentally demonstrated the relevance of this methodology.